2013
DOI: 10.1111/geb.12061
|View full text |Cite
|
Sign up to set email alerts
|

Olive trees as bio‐indicators of climate evolution in the Mediterranean Basin

Abstract: Aim This paper aims to project areas of olive cultivation into future scenarios. Accordingly, we first asked the question whether global circulation models (GCMs) are able to reproduce past climatic conditions and we used historical ranges of olive cultivation as a palaeoclimate proxy.Location The Mediterranean basin. MethodsWe used an ecological model, calibrated and validated for modern times, to test the reliability of a general circulation model (NCAR-CSM GCM) in reproducing past ranges of olive tree culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 43 publications
(35 reference statements)
4
47
0
Order By: Relevance
“…The northwest shift found in this study was in agreement with the general observation that distributions of plant species would shift towards the poles under global warming [48,49]. Our results were similar to findings of several studies on the effects of climate change on distribution of woody oil plants, such as Sapium sebiferum in the United States [50], Olea europaea L. in the Mediterranean basin [51,52], and Hevea brasiliensis (Willd. ex A.…”
Section: Changes Of the Distribution Range Of S Mukorossisupporting
confidence: 93%
“…The northwest shift found in this study was in agreement with the general observation that distributions of plant species would shift towards the poles under global warming [48,49]. Our results were similar to findings of several studies on the effects of climate change on distribution of woody oil plants, such as Sapium sebiferum in the United States [50], Olea europaea L. in the Mediterranean basin [51,52], and Hevea brasiliensis (Willd. ex A.…”
Section: Changes Of the Distribution Range Of S Mukorossisupporting
confidence: 93%
“…europaea, respectively) that have quite similar pollen morphology (Roselli, 1979;Ribeiro et al, 2012;Messora et al, 2017). Another problem arises from the fact that O. europaea is an evergreen xerophilous tree, whose growth is promoted by a warming climate (Moriondo et al, 2013). Recent studies have demonstrated that a seasonal analysis is required to establish robust relationships between the Mediterranean climate and olive development (Aguilera et al, 2015); therefore, an increasing trend in the pollen curves may have ambiguous significance in the diagrams from the Mediterranean Holocene records.…”
Section: Introductionmentioning
confidence: 99%
“…Under the context of climate change, the fundamental vegetative and reproductive phases of numerous plant species, such as the olive tree, might have serious problems in their adaptation to the new scenarios (Moriondo et al, 2013;Orlandi et al, 2014). The processes of pollination, fruit setting, and fruit maturation might be negatively affected, which are aspects to highlight, given the socio-economical importance of olive groves and their products for countries in the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of climate change on the Mediterranean olive-growing areas might depend on how these changes in temperature and rainfall patterns occur. In this way, a recent study discussed how some typical areas of olive cultivation might be particularly sensitive to projected climate change, and above all, the southern Mediterranean areas, which might become unsuitable for olive cultivation (Moriondo et al, 2013). As changes in climate can cause serious imbalances to physiological and biological rhythms of natural and cultivated plant species, models that predict phenological stages can be used to study the responses of plant life-cycle to global warming (Chuine et al, 1999;García-Mozo et al, 2008;Orlandi et al, 2014).…”
mentioning
confidence: 99%